2019
DOI: 10.1136/openhrt-2018-000994
|View full text |Cite
|
Sign up to set email alerts
|

Standardising practice in cardiology: reducing clinical variation and cost at Ochsner Health System

Abstract: ObjectiveLow quality and unwarranted clinical variation harm patients and increase unnecessary costs. Effective approaches to improve clinical and economic value have been difficult. The Ochsner Health System looked to improve clinical care quality and reduce unnecessary costs in cardiology using active measurement and customised feedback.MethodsWe serially measured care decisions using online, simulated cases to capture clinical details of cardiology practice and provide individual feedback. Fifty cardiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Overall, case-based VPS education significantly improved the percentage of appropriate decisions made for patients with PE. Other studies that used simulation with clinical guidance have also reported positive results [ 24 , 25 ]. In our analysis, cardiologists and haem-oncs showed significant improvements in all areas identified as gaps: Gap 1: risk stratification – a greater proportion are now ordering appropriate tests for risk stratification; Gap 2: monitoring patients to gauge adherence to therapy – a greater proportion are selecting patient-centred care strategies to improve adherence; Gap 3: applying the latest data on NOACs in patients with cancer – a greater proportion are now tailoring anticoagulant therapies based on patient presentation.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, case-based VPS education significantly improved the percentage of appropriate decisions made for patients with PE. Other studies that used simulation with clinical guidance have also reported positive results [ 24 , 25 ]. In our analysis, cardiologists and haem-oncs showed significant improvements in all areas identified as gaps: Gap 1: risk stratification – a greater proportion are now ordering appropriate tests for risk stratification; Gap 2: monitoring patients to gauge adherence to therapy – a greater proportion are selecting patient-centred care strategies to improve adherence; Gap 3: applying the latest data on NOACs in patients with cancer – a greater proportion are now tailoring anticoagulant therapies based on patient presentation.…”
Section: Discussionmentioning
confidence: 98%
“…Physician-level ordering did not serve as the focus of this work, unlike cost management strategies described elsewhere 25 26. While physicians did support select improvement projects, it proved more feasible to focus on nurse-driven performance in areas like throughput and staff scheduling.…”
Section: Limitationsmentioning
confidence: 99%
“…CPV patient simulations have been used in community and academic oncology practices, [9][10][11][12] and care decisions made in the simulations have been validated against standardized patients and chart abstraction. [13][14][15][16][17][18][19] CPVs are online patient vignettes in which providers proceed through the domains of a simulated clinical encounter-taking the history, conducting the physical exam, ordering as many or as few diagnostic tests as desired, making the diagnosis, and outlining a treatment and follow-up plan for the patient. To accurately measure clinical practice, simulations are interactive and open ended, rather than multiple choice.…”
Section: Clinical Performance and Value Simulation Datamentioning
confidence: 99%